Aeroelastic flutter energy harvesters self-polarized by triboelectric effects. (12th December 2017) - Perez, M; Boisseau, S; Geisler, M; Gasnier, P; Willemin, J; Despesse, G; Reboud, J L
Abstract: This paper presents the performances of several electrostatic flutter energy harvesters tested in a wind tunnel between 0 and 20 m s −1 . The main idea is to use the flutter capability of thin flexible films confined between lateral walls to induce simultaneously the capacitance variations and the electrostatic polarization required by the triboelectric/electrostatic conversion. This technology provides thin and flexible devices and solve the electret's stability issue (Perez et al 2015 Smart Mater. Struct., Perez et al 2015 New Circuits and Systems ). Our prototypes (<16 cm 2 ) have a quick startup (from 3 m s −1 ) and an electrical power-flux density from 0.35 μ W cm −2 @3 m s −1 (light breeze) to 35 μ W cm −2 @20 m s −1 (fresh gale). A Maximum Power Point circuit has been developed to efficiently use the power provided by the energy harvesters. The energy harvester combined with its power management circuit has finally been used to supply an 868 MHz wireless sensor node with temperature and acceleration measurements, validating the complete energy harvesting chain.